Tingkat Literasi Digital Mahasiswa Program Studi Perpustakaan dan Ilmu Informasi Universitas Negeri Padang - Fikri, Muhammad; Erlianti, Gustina (Departemen Informasi Perpustakaan dan Kearasipan, 2024)
The aim of this research is to determine the digital literacy level of students in the 2021 Padang State University Library and Information Science Study Program. The type of research used is a descriptive research method with a quantitative approach using a total sample. Data collection was carried out through questionnaires and data analysis using data description, data analysis, validity and reliability tests and then drawing conclusions. The research results show that the average gain score on the internet searching indicator is 3.11 (high category), the average gain score on the hypertext navigation indicator is 2.82 (high category) , the average score on the information content evaluation indicator (content evaluation) is 3.05 (high category), and the average score on the knowledge assembly indicator is 3.09 (high category). Based on this data, it can be concluded that the digital literacy level of the 2021 students of the Padang State University Library and Information Science Study Program has a high level of digital literacy, with an average score of 3.02 (high category).